2020
DOI: 10.24191/abrij.v6i1.9945
|View full text |Cite
|
Sign up to set email alerts
|

Influencing Factors in Dietary Supplement Consumption among University Students

Abstract: In recent years, there has been an increasing interest in consuming dietary supplements which believed to promote a healthy lifestyle among generations. However, lack of knowledge and peer pressure can be the problems despite its long success. Thus, the aim of this study is twofold; i) to assess the sociodemographic information among the students on taking dietary supplements and ii) to examine the influencing factors that lead to dietary supplements consumption among undergraduate students in Selangor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…However, some healthcare professionals must possess the knowledge and experience of the three selected DS. They could not consult or advise consumers on the usage and benefits of these products (7). This leads to consumers needing more confidence to approach healthcare professionals for further clarification.…”
Section: Kap Regarding the Three Selected Dietary Supplements (Bg Wg ...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, some healthcare professionals must possess the knowledge and experience of the three selected DS. They could not consult or advise consumers on the usage and benefits of these products (7). This leads to consumers needing more confidence to approach healthcare professionals for further clarification.…”
Section: Kap Regarding the Three Selected Dietary Supplements (Bg Wg ...mentioning
confidence: 99%
“…Besides, 75% of individuals in developing countries take one or more DS (6). In European countries, the DS intake prevalence was higher in northern than in the southern countries (7). Meanwhile, South Korea showed a high demand for taking DS, where 60% of people was higher than in other countries (7), whereas, in Malaysia, 25% of adults consumed DS (8).…”
Section: Introductionmentioning
confidence: 98%
“…Besides, a recent research study among university students in Jordan revealed that the body mass index (BMI) and dietary supplements showed a significant direct association, whereby students with higher BMI was likely to consume dietary supplement (Elsahoryi et al, 2023). In contrast, some studies found that adults with normal BMI consumed significantly more dietary supplements (Aziz et al, 2020;Mohd Ashri et al, 2021;Žeželj et al, 2018). Nevertheless, there is also a study that claimed that lower BMI was associated with dietary supplement intake (Jeon et al, 2021).…”
Section: Introductionmentioning
confidence: 96%